2012
DOI: 10.3102/0002831211434596
|View full text |Cite
|
Sign up to set email alerts
|

A Course on Effective Teacher-Child Interactions

Abstract: Among 440 early childhood teachers, half were randomly assigned to take a 14-week course on effective teacher-child interactions. This course used the Classroom Assessment Scoring System (CLASS) as the basis to organize, describe, and demonstrate effective teacher-child interactions. Compared to teachers in a control condition, those exposed to the course reported more intentional teaching beliefs and demonstrated greater knowledge of and skills in detecting effective interactions. Furthermore, teachers who to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(119 citation statements)
references
References 72 publications
(109 reference statements)
4
108
0
7
Order By: Relevance
“…For instance, as van 5 Teaching style has been used as a key concept in educational research, particularly regarding education for older children and adults during the 1980s and 90s (e.g., Conti, 1985;Goudas, Biddle, Fox, & Underwood, 1995). During the first decade of the 21 st century, the topic of teaching practices has become more prevalent and its focus has increasingly been on teacher-child classroom interaction (e.g., Hamre et al, 2012;Pianta, 1999), considering both parties in the teaching process. In this study, the term practices refers to a teacher's systematic, conscious activity, which is also affected by the teacher's personal values and his or her conception of the child as a learner; hence, referring to teachers' practices as taking place in the interactive system of preschool classrooms (Greeno et al, 1998).…”
Section: Teachers' Pedagogical Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, as van 5 Teaching style has been used as a key concept in educational research, particularly regarding education for older children and adults during the 1980s and 90s (e.g., Conti, 1985;Goudas, Biddle, Fox, & Underwood, 1995). During the first decade of the 21 st century, the topic of teaching practices has become more prevalent and its focus has increasingly been on teacher-child classroom interaction (e.g., Hamre et al, 2012;Pianta, 1999), considering both parties in the teaching process. In this study, the term practices refers to a teacher's systematic, conscious activity, which is also affected by the teacher's personal values and his or her conception of the child as a learner; hence, referring to teachers' practices as taking place in the interactive system of preschool classrooms (Greeno et al, 1998).…”
Section: Teachers' Pedagogical Practicesmentioning
confidence: 99%
“…Concrete teachers' practices that have been associated with classroom organisation include for instance the use of proactive discipline strategies, showing consistent behavioural expectations, minimising downtime, and using a variety of strategies and modalities during instruction (Pianta, La Paro, et al, 2008). In addition, teachers' efficient use of time, giving children more opportunities to learn, has been found to enhance organisationally supportive interactions (Hamre et al, 2012;Howes et al, 2008).…”
Section: Teacher-child Interactions In the Teaching Through Interactimentioning
confidence: 99%
“…Afterwards, researchers and program makers will be able to design programs pertaining to needs of support in teachers' areas of educational and developmental experiences of children, and importance to children's learning outcomes in early childhood. Considering early child is an important period where children develop important developmental and learning outcomes, supporting teachers in their scaffolding of children's learning and development could be an essential part of the early childhood education (Curby et al, 2009;Hamre et al, 2012;Fantuzzo et al, 2012;Pianta, 1999).…”
Section: Child Development and Education In The Preschool Years 43mentioning
confidence: 99%
“…In sum, teachers are important agents of the development and education of young children (Pianta, 1999), because children's academic, social, emotional, and linguistic growth during preschool period is greatly CHILD DEVELOPMENT AND EDUCATION IN THE PRESCHOOL YEARS 37 influenced by the teacher related issues, such as the quality of teacher-child interactions (Curby et al, 2009;Hamre et al, 2012;Fantuzzo et al, 2011), teacher qualifications, and teacher-students ratio in classrooms (Gorey, 2001). Main characteristics of teachers regarding child development and education are classroom management, teaching strategies, emotional, organizational, and instructional support (Pianta, La Paro, & Hamre, 2008) and teacher-student interactions are quite important for student learning .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, four groups were created by crossing the Phase I Course/Control groups with the Phase II Coaching/Control groups. A full description of the intervention, study design, sample, and results can be found in Hamre et al (2012) and Downer et al (in press). …”
Section: Methods Participants and Selectionmentioning
confidence: 99%